Nahum : a new translation with introduction and commentary - Christensen, Duane L., 1938- (New Haven : Yale University Press, 2009)
This volume represents a significant breakthrough in the study of Hebrew prosody with important implications for understanding the formation of the canon of the Hebrew Bible. Duane Christensen, a renowned biblical scholar, offers a detailed analysis of the Hebrew text of Nahum and demonstrates the intricate literary structure and high poetic quality of the work. Nahum is a book about God's justice and portrays God as strong, unyielding, and capable of great anger. This view of God's nature stands in contrast to that found in Jonah, another book in the section of the Hebrew Bible known as the Book of the Twelve Prophets, which presents God as "compassionate, gracious.... and abounding in steadfast love." Christensen shows how Nahum and Jonah present complementary aspects of God's nature, each essential for an understanding of the divine being.
Includes bibliographical references (p. 67-148) and indexes.
Keywords: Bible. -- Commentaries